Habituation Method in Developing Children's Independent Character at Madrasah Ibtidaiyah - Herson Anwar; Kartini Dwi Hasanah (Yayasan Adra Karima Hubbi, 2024)
Background. Accustoming children to the character of independence is not only beneficial during childhood, but also has an impact on the child's future when they are adults. Therefore, it is necessary to measure children's level of independence from childhood so that teachers can know the level of development of their students' independence and can carry out learning activities that can improve and increase children's independence at school. Purpose. The aim of this research was to implement the habituation of children's independent character from elementary age so that teachers can find out the level of development of their students' independence and can carry out learning activities that can improve and increase children's independence in madrasah ibtidaiyah. Method. The type of research used in this research is quantitative descriptive research to obtain a picture of children's independence among students at Madrasah Ibtidiyah by looking at three indicators of children's independence at Madrasah Ibtidiyah. The subjects in this research were madrasah ibtidaiyah students. The data obtained was then analyzed using a descriptive percentage formula. Results. The results of the research showed that the method for habituating children's independent behavior in Ibtidaiyah madrasas is by designing activities, whether routine, spontaneous or programmed activities. The habit of character independence can be implemented through the class picket program, arriving on time, washing hands before entering class, doing assignments given by the teacher yourself without cheating, taking and returning books read in the library, and many other examples. Conclusion. These habits can be applied to encourage independent behavior in children.